The Empowerment Of Community Communication Network For Dissemination Of Disaster Information In Dayeuhkolot Bandung - Nuning Kurniasih; Engkus Kuswarno; Suwandi Sumartias; Nindi Aristi; Evie Ariadne Shinta Dewi (LPPM of NAROTAMA UNIVERSITY, 2018)
Dayeuhkolot Sub-district is an area which prone to the flood disaster. For decades, the regional has been flooded in every rainy season. There are several things that caused the flood disaster in Dayeuhkolot Sub-district, such as due to the existence of its territory which is between Citarum River Basin (Citarum) and Cikapundung River, the planning of the less good area and many piles of garbage. The flood disaster will certainly result in many losses, either loss of property, psychological or loss of life. However, it is expected with the cooperation of many various elements, the loss can be minimized. One effort that can minimize the effects of this flood disaster is by the dissemination of disaster information. The dissemination of disaster information should empower the various communications networks that exist in the community so that the public will be more concerned about the various disaster that might befall them and prepare for the possibility of the disaster. The activities undertaken to achieve this goal is through Focus Group Discussion (FGD) and counseling. FGD was conducted by inviting the resource persons from the Regional Disaster Management Agency (BPBD), village and sub-district officials, disaster volunteer and other elements in Dayeuhkolot Sub-district. FGD and counseling was attended by 16 representatives from Dayeuhkolot sub-district, 1 source from BPBD and 5 PPM Priority Team from Fikom Unpad. All FGD participants and counseling are active in responding and entering on the issues related to the disaster information dissemination. The result of this PPM activity become an entry for BPBD in increasing the community participants, especially for those who are the members of community communication network nodes to play a role in disseminating disaster information. BPBD will also convey this input to the related parties in order to empower the community communication network more optimally.